Role of Lung Microbiome in Innate Immune Response Associated With Chronic Lung Diseases - Paudel, Keshav Raj; Dharwal, Vivek; Patel, Vyoma K.; Galvao, Izabela; Wadhwa, Ridhima; Malyla, Vamshikrishna; Shen, Sj Sijie; Budden, Kurtis F.; Hansbro, Nicole G.; Vaughan, Annalicia; Yang, Ian A.; Kohonen-Corish, Maija R J; et al. (Frontiers in Medicine, 2020)
Respiratory diseases such as asthma, chronic obstructive pulmonary disease (COPD), lung fibrosis, and lung cancer, pose a huge socio-economic burden on society and are one of the leading causes of death worldwide. In the past, culture-dependent techniques could not detect bacteria in the lungs, therefore the lungs were considered a sterile environment. However, the development of culture-independent techniques, particularly 16S rRNA sequencing, allowed for the detection of commensal microbes in the lung and with further investigation, their roles in disease have since emerged. In healthy individuals, the predominant commensal microbes are of phylum Firmicutes and Bacteroidetes, including those of the genera Veillonella and Prevotella. In contrast, pathogenic microbes (Haemophilus, Streptococcus, Klebsiella, Pseudomonas) are often associated with lung diseases. There is growing evidence that microbial metabolites, structural components, and toxins from pathogenic and opportunistic bacteria have the capacity to stimulate both innate and adaptive immune responses, and therefore can contribute to the pathogenesis of lung diseases. Here we review the multiple mechanisms that are altered by pathogenic microbiomes in asthma, COPD, lung cancer, and lung fibrosis. Furthermore, we focus on the recent exciting advancements in therapies that can be used to restore altered microbiomes in the lungs.